Integrin α3 mutations with kidney, lung, and skin disease - Has, Cristina; Straub, Beate Katharina; Haußer-Siller, Ingrid (The New England journal of medicine, 2012)
From the Department of Dermatology, University Freiburg Medical Center, Freiburg (C.H., D.K., Y.H., P.E., L.B.-T.), and the Departments of Pathology (B.K.S.) and Dermatology (I.H.), University of Heidelberg, Heidelberg — both in Germany; the Departments of Pediatric Nephrology (G.S., G.F.L.), Dermatology (L.W.), and Pulmonology (A.M.), Children’s Hospital Zurich, and the Department of Dermatology, University Hospital Zurich (L.W.) — both in Zurich; the Department of Pediatrics, University of Michigan, Ann Arbor (V.-V.W., F.H.); University College London Institute of Child Health and Great Ormond Street Hospital for Children National Health Service Trust, London (A.W., D.B.); and the Metabolic Disease Unit (Y.A.) and the Pediatric Stem Cell Research Institute and Division of Pediatric Nephrology (B.D.), Edmond and Lily Safra Children’s Hospital, Sheba Medical Center, Sackler School of Medicine, Tel Aviv University, Tel Aviv. Address reprint requests to Dr. Spartà at the University Children’s Hospital, Steinwiesstr. 75, CH-8032 Zurich, Switzerland, or at giuseppina.spartakispi.uzh.ch.